The Influence of the Treffinger Learning Model on Process Skills and Geography Learning Outcomes of Students at MAN 2 Ambon - Lasaiba, Mohammad Amin; Lasaiba, Irvan (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2022)
The Treffinger learning model is one of the instructional models that develop divergent thinking skills. This research is a quasi-experimental study. The research design used is a Pre-test Post-test design, which is a quasi-experimental design that investigates the level of similarity between groups. The study was designed with two groups: an experimental group and a control group. This research was conducted at SMP Negeri 14. The population in this study consisted of eighth-grade students, with two classes randomly selected. The data obtained in this study is quantitative, in the form of process skills test results and science learning outcomes tests. The data analysis techniques used include descriptive analysis and multivariate analysis (MANOVA) with the assistance of SPSS 26.0 for Windows. The results of the study showed that the process skills and learning outcomes of students taught using the Treffinger model, based on the F-value analysis (F = 0.116) with a significance level of less than 0.05, indicate significant differences in process skills and learning outcomes between the groups using the Treffinger model and those using conventional methods. The difference in the average scores of process skills and learning outcomes, determined using the Least Significant Difference (LSD) method, was 1.651 with a significance level of less than 0.05. This indicates that the learning outcomes achieved by students taught using the Treffinger model are better compared to those taught using conventional methods.